Currency swap valuation - Atakhanov, Bekhzod (2012)
This paper analyses the valuation methods of currency swaps, studying the valuation technique applied in each, highlighting the differences and shortcomings. Swaps being one of the highly adaptable financial instruments and the fact that are traded OTC obliged the pricing method to be flexible, as no comparison of market and model prices is attainable. Considered valuation approaches are based on interest rate swap valuation and deeply covered the relations between discount curves, forward rates and zero-coupon bonds. Zero-coupon method, discount curve method, modified discount curve method and its combination are considered as a target group for the research. Results are interpreted according to the reviewed literature.